Blurring global epistemic boundaries: The emergence of traditional knowledge in environmental governance - Andrés López-Rivera (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2020)
In the wake of the 1992 Earth Summit in Rio de Janeiro, 'traditional knowledge' became a recurring theme in global environmental governance. The emergence of traditional knowledge in a governance field marked by global science begs the following question: how is it that a particular set of intellectual activities other than science came to be perceived as a form of knowledge whose attributes are valuable for governing the global environment? This paper aims to grapple with this question by tracing the emergence of the category of traditional knowledge in global environmental governance. The main argument is that traditional knowledge came to be conceived of as a cognitive resource with utilitarian and 'glocal' properties through a series of interventions on the part of public scientists and landmark environmental reports that blurred the boundaries between science and nonscience. Building upon the concept of boundary work in Science and Technology Studies, this paper puts forth the concept of boundary blurring to analyze how aspects of science are attributed to traditional knowledge, thus attenuating the demarcation between science and other forms of knowledge. Boundary blurring works as a form of legitimation of traditional knowledge and, through the attribution of knowledge to nonscientific actors, opens up a space for these to make knowledge claims in global governance processes. Ultimately, the analysis throws light on the constitution of unconventional 'knowledge actors' in global governance, in particular indigenous peoples and local communities.
urn:nbn:de:hbz:464-20200617-133235-5
Keywords: 320; Boundary blurring; Traditional knowledge; Indigenous peoples; Global environmental governance